Mannitol 1-phosphate metabolism is required for sporulation in planta of the wheat pathogen Stagonospora nodorum - Solomon, P.; Tan, Kar-Chun; Oliver, Richard (AMER PHYTOPATHOLOGICAL SOC, 2005)
An expressed sequence tag encoding a putative mannitol 1-phosphate dehydrogenase (Mpd1) has been characterized from the fungal wheat pathogen Stagonospora nodorum. Mpd1 was disrupted by insertional mutagenesis, and the resulting mpd1 strains lacked all detectable NAD-linked mannitol I-phosphate dehydrogenase activity (EC 1.1.1.17). The growth rates, sporulation, and spore viability of the mutant strains in vitro were not significantly different from the wild type. The viability of the mpd1 spores when subjected to heat stress was comparable to wild type. Characterization of the sugar alcohol content by nuclear magnetic resonance spectroscopy revealed that, when grown on glucose, the mutant strains contained significantly less mannitol, less arabitol, but more trehalose than the wildtype strains. The mannitol content of fructose-grown cultures was normal. No secreted mannitol could be detected in wild type or mutants. Pathogenicity assays revealed the disruption of Mpd1 did not affect lesion development, however the mutants were unable to sporulate. These results throw new light on the role of mannitol in fungal plant interactions, suggesting a role in metabolic and redox regulation during the critical process of sporulation on senescing leaf material.